2018
DOI: 10.1021/acs.jpcc.8b01296
|View full text |Cite
|
Sign up to set email alerts
|

CH3Cl/Cu(410): Interaction and Adsorption Geometry

Abstract: The Rochow process is the most common technology used to prepare organosilicon compounds on an industrial scale, and yet the mechanism is still not well understood. It involves the reaction of methyl chloride (CH3Cl) with silicon, catalyzed by copper. To understand the elementary steps of the reaction involved, we studied the molecular adsorption of CH3Cl/Cu­(410) at 100 K and its complete desorption at higher temperatures, 100 K < T D < 200 K. Temperature-programmed desorption (TPD) spectra show two CH3Cl des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…The absolute differences between literature and the herein reported values are within what is considered quantum chemical accuracy and can be ascribed to different applied functionals and computational settings. Makino et al showed experimentally that at low coverage physisorption is possible with the C–Cl bond either perpendicular or parallel to the [001] plane of the Cu(410) surface and that at higher coverage the perpendicular adsorption geometry was dominant. In the present study the adsorption energies without ZPE of CH 3 Cl on different Cu(410) sites range from −0.02 to −0.30 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute differences between literature and the herein reported values are within what is considered quantum chemical accuracy and can be ascribed to different applied functionals and computational settings. Makino et al showed experimentally that at low coverage physisorption is possible with the C–Cl bond either perpendicular or parallel to the [001] plane of the Cu(410) surface and that at higher coverage the perpendicular adsorption geometry was dominant. In the present study the adsorption energies without ZPE of CH 3 Cl on different Cu(410) sites range from −0.02 to −0.30 eV.…”
Section: Resultsmentioning
confidence: 99%
“…underpin the catalytic capacity of copper-terminated (100) surface with other copper terminations, we have contrasted our obtained activation energies for dissociation reactions in selected halogenated hydrocarbons molecules with corresponding values ensued over another copper termination surface (i.e., Cu(410))[61]. FigureS1(in the supplementary materials) shows that fission of the C-Cl bond in the CH3Cl molecule over copper-terminated (410) requires slightly higher activation barrier (10.3 kcal mol -1 ) in reference to the value calculated here for the clean Cu(100) surface; i.e., 8.3 kcal mol -1 .…”
mentioning
confidence: 99%
“…80 years after the independent discovery by R. Müller and E. G. Rochow, the direct synthesis reaction, given in eqn (1), remains the most common method for the synthesis of organosilicon compounds. [1][2][3][4][5][6][7] Si(s) + 2CH 3 Cl(s) → (CH 3 ) 2 SiCl 2 (g) (1) It is an important industrial process with a high amount of silicones produced per year (2.4 million metric tons in 2019) 8 with major applications such as construction, electronics, transportation, medical, personal care and others. 5 Therefore, the optimization of the silicones production via the increase in production yield is crucial as well as better energy efficiency and raw materials utilization and lower greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, the optimization of the silicones production via the increase in production yield is crucial as well as better energy efficiency and raw materials utilization and lower greenhouse gas emissions. For the direct synthesis, silicon powder is mixed with a copper-based catalyst [1][2][3][4][5] and gaseous CH 3 Cl in a fluidized bed reactor at temperature and pressure ranging between 280-350 °C and 1-10 bar. 9,10 The nature of the copper precursor strongly influences the catalytic performance and promoters such as Zn, Sn, Al and P contribute to increase the activity, stability, and selectivity toward chlorosilanes 5,7,[10][11][12][13][14][15][16] (mostly desired dimethyldichlorosilane, but also methylchlorosilane, trimethylchlorosilane, methyldichlorosilane, dimethylchlorosilane and tetramethylsilane).…”
Section: Introductionmentioning
confidence: 99%